Dupuytren Disease: A Retrospective Cohort Study Comparing Collagenase Injection and Percutaneous Needle Fasciotomy. Issue 10 (24th October 2022) - Mehdiyev, Turkhan; Maffei, Davide; Müller, Verena; Mair, Waltraud; Zimmermann, Robert F.; Baur, Eva-Maria
Abstract : Background: Collagenase Clostridium histolyticum (CCH) injection and percutaneous needle fasciotomy (PNF) are minimally invasive procedures aiming to relieve Dupuytren disease (DD) by disrupting the cord and restoring the normal functionality of the hand. The purpose of this study is to compare the outcomes and recurrence rates for treatment of DD in the proximal interphalangeal (PIP) and metacarpophalangeal (MCP) joints with either collagenase or percutaneous needle at 3-year follow-up. Moreover, we aim to determine the role of these therapeutic modalities and their impact on hand functionality and quality of life. Methods: In this retrospective analysis, we compare treatment outcomes in 35 patients, of whom 22 were treated with PNF and 13 with CCH injection. Results: The mean outcome in contracture degrees at 3-year follow-up was 9 degrees for MCP joints for both treatment groups, 34 degrees for PNF, and 28 degrees for CCH for PIP joints. There was no statistical significance between the treatment groups in MCP joints ( P = 0.786) or in PIP joints ( P = 0.474). Contracture recurrences were similar in PIP joints of both groups and greater in MCP joints in the CCH group compared to PNF. The Disabilities of the Arm, Shoulder, and Hand and the Unité Rhumatologique des Affections de la Main scores showed a reduction in impairment in both groups without significant differences between the two groups. Conclusions: The results of this study show that PNF appears to be as effective and minimally invasive as CCH injection, but at significantly lower cost. Considering these factors, the authors prefer and recommend the use of PNF over CCH.